Seasonal variation and recent status of Typhoid Fever in a tertiary care hospital - Soomro, Samreen; Baig, Samina; Naseem, Saima; Sharafat, Shaheen (International Journal of Endorsing Health Science Research, 2014)
In many developing countries, typhoid fever is endemic. Early diagnosis is important for appropriate treatment on time. Typhi dot is important diagnostic tool for early diagnosis of typhoid fever. In the current study from February, 2012 to May 2014, samples from 19433 febrile cases referred to Dow Diagnostic Research and Reference lab were screened for serum IgM and IgG for Salmonella typhi by Typhi dot test. Results showed that about 12501 patients had both IgM and IgG antibodies against Salmonella typhi. Male patients were more commonly affected than female patients. Highest frequency of positive cases was seen during the month of October. Age group >15-44 was most likely affected among different age groups. This study suggested that still we are far behind in improving sanitation and elimination of such controllable disease. Therefore prompt measures should be taken to control the disease especially during hot season by vaccination, improved sanitation and education as well.